PERAN SUPERVISOR DALAM PENINGKATAN MUTU PENDIDIKAN - Ainol; Didik Heriadi (UNZAH Genggong, 2020)
Education is a very important thing to improve, because through the education of the nation's generation that is qualified in terms of science and technology and imtaq can be formed. To improve the quality of education, the parties involved must also be constantly improved. One of the parties that plays a role in the world of education is the school supervisor. Quality school supervisors must have a large responsibility, always develop their profession, carry out the preparation of work methods and school supervision instruments, and have a clear work program in accordance with the stipulated provisions. Management of education supervisors is a strategic element in achieving educational goals. Both the purpose of education in the national, institutional, and also curricular context. Keywords: supervisor, education, and nation's generation